Morpho-anatomical characterization of embryogenic calluses from immature zygotic embryo of peach palm during somatic embryogenesis - DOI: 10.4025/actasciagron.v32i2.3248 - Maciel, Simone Alencar; Fermino Junior, Paulo Cesar Poeta; Silva, Ricardo Alexandre; Scherwinski-Pereira, Jonny Everson (Acta Scientiarum. Agronomy, 2010)
The objective of this study was to morpho-anatomically characterize nodular embryogenic calluses from zygotic embryos of peach palm during the induction of somatic embryogenesis. Immature zygotic embryos were pre-treated in MS medium added to Picloram and 2,4-D (25 µM) and BAP (0, 5, 10 µM). After three months, primary calluses were transferred to MS induction medium added to Picloram and 2,4-D (450 µM). After six months, the embryogenic calluses were then histologically analyzed and cultivated in the maturation medium. The competent tissues of the zygotic embryos differentiated embryogenic calluses under action of both Picloram and 2,4-D auxins (450 µM), where the presence of multi-granular structures were observed. Histological observations showed that in the nodular embryogenic calluses, the outlying parenchymal cells exhibit cellular characteristics of high mitotic activity. Differentiation of tracheal elements exists in embryogenic calluses connecting the callus to the explant. The evaluated cytokinin/auxin interaction influences the development of embryogenic calluses and globular structures.